Implementasi Nilai-Nilai Pancasila Dengan Akulturasi Inovasi Teknologi Untuk Mencapai Effisiensi Pada Kegiatan Pemasaran dan Perdagangan Migas di Indonesia - Edy Soesanto; Divka Octavia Nurrochim; Sendy Dewanto (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The use of technology has become the main key in increasing efficiency in the oil and gas marketing and trading industry. This research investigates the implementation of Pancasila values ​​in the context of acculturation of technological innovation to increase efficiency in oil and gas marketing and trading activities in Indonesia. Through literature analysis, this research identifies Pancasila values ​​as a moral and ethical foundation that can guide positive transformation in business practices. This research also explores how technological innovations, such as digitalization and automation, can be combined with Pancasila values ​​to create a more efficient and sustainable system in the oil and gas industry. It is hoped that the results of this research will provide a better understanding of how technology influences efficiency in oil and gas marketing and trading, as well as provide useful recommendations for the oil and gas industry to utilize technology in accordance with the reference value of "Social Justice for All Indonesian People" in order to create fair distribution. and equitable distribution of oil and gas resources for the benefit of all Indonesian people. In this context, implementing the 5th principle means ensuring that the economic and social benefits of the oil and gas industry are not only enjoyed by a few people or regions, but are distributed fairly to all levels of society. This could include sharing income from oil and gas activities, environmental protection, and creation equal employment opportunities.